Secular New Zealand and Religious Diversity: From Cultural Evolution to Societal Affirmation - Pratt, Douglas (Social Inclusion, 2016)
About a century ago New Zealand was a predominantly white Anglo-Saxon Christian nation, flavoured only by diversities of Christianity. A declining indigenous population (Maori) for the most part had been successfully converted as a result of 19th century missionary endeavour. In 2007, in response to increased presence of diverse religions, a national Statement on Religious Diversity was launched. During the last quarter of the 20th century the rise of immigrant communities, with their various cultures and religions, had contributed significantly to the changing demographic profile of religious affiliation. By early in the 21st century this diversity, together with issues of inter-communal and interreligious relations, all in the context of New Zealand being a secular society, needed to be addressed in some authoritative way. Being a secular country, the government keeps well clear of religion and expects religions to keep well clear of politics. This paper will outline relevant historical and demographic factors that set the scene for the Statement, which represents a key attempt at enhancing social inclusion with respect to contemporary religious diversity. The statement will be outlined and discussed, and other indicators of the way in which religious diversity is being received and attended to will be noted.